Evidence for a high-z ISW signal from supervoids in the distribution of eBOSS quasars. Issue 1 (7th April 2022) - Kovács, A; Beck, R; Smith, A; Rácz, G; Csabai, I; Szapudi, I
ABSTRACT: The late-time integrated Sachs-Wolfe (ISW) imprint of $R\gtrsim 100~h^{-1}\, Mpc$ superstructures is sourced by evolving large-scale potentials due to a dominant dark energy component in the ΛCDM model. The aspect that makes the ISW effect distinctly interesting is the repeated observation of stronger-than-expected imprints from supervoids at z ≲ 0.9. Here we analyse the un-probed key redshift range 0.8 < z < 2.2 where the ISW signal is expected to fade in ΛCDM, due to a weakening dark energy component, and eventually become consistent with zero in the matter dominated epoch. On the contrary, alternative cosmological models, proposed to explain the excess low- z ISW signals, predicted a sign-change in the ISW effect at z ≈ 1.5 due to the possible growth of large-scale potentials that is absent in the standard model. To discriminate, we estimated the high- z ΛCDM ISW signal using the Millennium XXL mock catalogue, and compared it to our measurements from about 800 supervoids identified in the eBOSS DR16 quasar catalogue. At 0.8 < z < 1.2, we found an excess ISW signal with A ISW ≈ 3.6 ± 2.1 amplitude. The signal is then consistent with the ΛCDM expectation ( A ISW = 1) at 1.2 < z < 1.5 where the standard and alternative models predict similar amplitudes. Most interestingly, we also observed an opposite-sign ISW signal at 1.5 < z < 2.2 that is in 2.7σ tension with the ΛCDM prediction. Taken at face value, these recurring hints for ISW anomalies suggest an alternative growth rate of structure in low-density environments at $\sim 100~h^{-1}\, Mpc$ scales.